Pengembangan Media Pembelajaran HAFWA Berbasis HTML5 Berpendekatan Pendidikan Matematika Realistik Pada Materi Bentuk Aljabar - Marsa Istiana Salsabila; Nanang Nabhar Fakhri Auliya (Program Studi Pendidikan Matematika FIP UNHASY, 2024)
The students’ problem in mastering algebraic is the lack of enthusiasm when learning mathematics, because learning is only centered on the teacher. Technology- based learning media innovations is the basic for the research to assist students comprehend the subject. This study's goal is to provide an overview of every development stage and also the HAFWA learning materials’ viability. This study is classified as Research and Development, and the data gathering tools include user response sheets and expert assessment sheets in the form of expert feasibility test questionnaires. The HAFWA learning media's feasibility level received an average score of 80.5 from experts in the subject, and an average score of 90.5 with